Desain E-Commerce Wahib Collection Dengan Business Model Canvas Untuk Meningkatkan Penjualan - Seftifin Ratna Manda; Atik Ariesta; Deni Mahdiana; Lauw Li Hin; Ratna Kusumawardani (Jurnal Ticom: Technology of Information and Communication, 2023)
Technological developments are now very rapid, one of which is the internet. The internet is the main topic in today's society, with the internet people are able to carry out various activities such as buying and selling goods online. Nowadays buying and selling are very easy with a viral business model, namely e-commerce, so customers don't have to come to the store to make a purchase transaction. Wahib Collection store is a store engaged in the sale of clothing. Products sold are various kinds of clothing such as negligees, women's clothing, t-shirts, pants, and jackets. The Wahib Collection store was founded in 2000 and is a family-owned business that has been passed down to their children. The Wahib Collection store has a problem, namely the Wahib Collection store markets its products only by opening store stalls in the market with marketing coverage only around the store, recording at the store is still done manually so the recording is not appropriate, there has been a decline in sales due to the Covid-19 pandemic implementing social distancing and people must comply with health protocols and avoid crowds so that the market is quiet. This is the background for utilizing e-commerce as a platform for selling and buying online. The purpose of this research is to make marketing reach wider, data recording will be stored correctly on the website, and sales can be made online. The methodology used is interviews, document analysis, and literature studies with the development of the system using Rapid Application Development (RAD). so that a sales information system is formed using the WordPress Content Management System (CMS). The Business Model Canvas (BMC) determines the proposed business model based on the current business model. The results of this study, customers can make purchases online using the website, they don't have to come to the store and the store records are computerized.